State Responsibility in Addressing Internally Displaced Persons (IDPs) Based on the International Legal Framework - Silviana, Ria (NEGREI: Academic Journal of Law and Governance, 2024)
Internally Displaced Persons (IDPs) are individuals forced to flee their homes due to armed conflicts, natural disasters, or environmental changes while remaining within their country’s borders. Unlike refugees, IDPs lack specific international legal protections under a binding framework, making them more vulnerable to inadequate state responses. This study explores the legal framework governing IDP protection, focusing on the Guiding Principles on Internal Displacement (GPID) and state responsibilities under international law. Using a normative legal research approach, this study examines primary legal sources such as the GPID, the Kampala Convention, and Indonesia’s national policies on internal displacement. Findings indicate that while the GPID provides a comprehensive yet non-binding framework, the Kampala Convention represents a regional effort to establish legally binding obligations for IDP protection. However, significant gaps persist at both international and national levels, particularly in enforcement mechanisms and state accountability. In Indonesia, IDP protection is primarily addressed through disaster management laws, social conflict resolution policies, and human rights regulations. The study highlights the need for stronger legal commitments, enhanced international cooperation, and more effective national implementation strategies to ensure the rights and dignity of IDPs are upheld.